2019
DOI: 10.1002/celc.201901394
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Nanoscale Pinhole Defects in Nitroaryl Layers with Scanning Electrochemical Cell Microscopy

Abstract: We are reporting the application of scanning electrochemical cell microscopy to probe and identify nanometric defects in a multilayered aryl film formed by aryldiazonium reduction. We have determined by numerical simulation that, due to pipette geometry restrictions, the best sensitivity towards pinhole size can be obtained when measuring small pinholes (� 10 nm) with moderately large pipette sizes (ca. 500 nm).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…In a conventional Ag/AgCl RE, an Ag/AgCl wire is immersed in a KCl solution with a constant Cl – activity and isolated from the test solution with a porous frit to limit the sample contamination, whereas the non-isolated Ag/AgCl wire serves as the quasi-reference counter electrode (QRCE) in the scanning electrochemical cell microscopy (SECCM), which is the advanced version of the scanning droplet cell technique. Single- and double-channel pipettes are the most commonly used in SECCM with one and two Ag/AgCl wires inserted, respectively. Herein, we explored the behavior of the Ag/AgCl wire QRCE in the single-channel micropipette SECCM, which is also called the scanning micropipette contact method (SMCM). , Although the potential stability of the Ag/AgCl QRCE has been confirmed under SMCM experimental conditions, , the effect of Ag + originating from the Ag/AgCl wire QRCE ( ) , on the currents (pA levels) measured in a SMCM experiment has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In a conventional Ag/AgCl RE, an Ag/AgCl wire is immersed in a KCl solution with a constant Cl – activity and isolated from the test solution with a porous frit to limit the sample contamination, whereas the non-isolated Ag/AgCl wire serves as the quasi-reference counter electrode (QRCE) in the scanning electrochemical cell microscopy (SECCM), which is the advanced version of the scanning droplet cell technique. Single- and double-channel pipettes are the most commonly used in SECCM with one and two Ag/AgCl wires inserted, respectively. Herein, we explored the behavior of the Ag/AgCl wire QRCE in the single-channel micropipette SECCM, which is also called the scanning micropipette contact method (SMCM). , Although the potential stability of the Ag/AgCl QRCE has been confirmed under SMCM experimental conditions, , the effect of Ag + originating from the Ag/AgCl wire QRCE ( ) , on the currents (pA levels) measured in a SMCM experiment has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, methods are available which make use of rotating disk electrodes with variable rotation rates 27 or scanning electrochemical cell microscopy. 28 …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the thinnest and most defective regions within a biomolecular film are the most heavily weighted during electrochemical measurements on macroelectrodes. Payne and Mauzerell reported that scanning electrochemical microscopy can be used to locate pinholes within aryldiazonium thin films [165]. Similarly, Jiang, Diao, Tong and co-workers used a combination of electrochemical methods to semi-quantitatively analyze defects within Au-thiol SAMs [166][167][168][169].…”
Section: Aryldiazonium-based Electrochemical Reductionmentioning
confidence: 99%